Acquired Long QT Syndrome and Electrophysiology of Torsade de Pointes - El-Sherif, Nabil (Arrhythm Electrophysiol Rev, 2019)
Congenital long QT syndrome (LQTS) has been the most investigated cardiac ion channelopathy. Although congenital LQTS remains the domain of cardiologists, cardiac electrophysiologists and specialised centres, the much more frequently acquired LQTS is the domain of physicians and other members of healthcare teams required to make therapeutic decisions. This paper reviews the electrophysiological mechanisms of acquired LQTS, its ECG characteristics, clinical presentation, and management. The paper concludes with a comprehensive review of the electrophysiological mechanisms of torsade de pointes.